A study of whole body vibration exposure for a bus driver along Kuantan to Johor Bharu - Siti Nur Atikah, Abdullah (2012)
In whole body vibration is important to be learned and discovered because it can reduce accidents. Statistics show accidents involving public transport such as buses are often happen. Therefore, a bus driver must be disclosed in more detail about the whole body vibration. This is because when a bus had a higher Whole Body Vibration throughout the body, the bus driver should take a rest for a moment before continuing his journey. The main purpose of this study was to investigate the Whole Body Vibrations (WBV) throughout the body to a bus driver who drives a bus in a sitting position. In addition, this study is to investigate the noise produced on the bus during the journey to the destination which is from Kuantan to Johor Bahru. There are two steps taken to obtain data which are survey questions as well as direct observation. For the survey, a total of 20 bus drivers were randomly selected to answer the survey form provided. The survey form consists of part A until G. Direct observation is a process where everything that happens along the way is recorded to facilitate discussions of the process. To obtain the value of whole body vibration and noise effects, instruments called dosimeter and accelerometer sensor is used. Accelerometer sensor is a device to measure the vibrations. This device is placed on the driver seat. Later, the bus driver would sit on the equipment along the way to the destination. Then, all data will be entered into a program at Quest Software to make graphs. Overall, the vibrations are recorded for 4jam of 0.5467 m / s ². Data were compared with data from ISO 2631. According to ISO 2631, for the time worked 4hours, RMS value is 4 m / s ². Thus, the value obtained shall not exceed the value of ISO 2631. For sound effects, the trip takes about 6 hours should not exceed 92dB. The results recorded are 95.6dB. This value exceeds its recoverable amount. Also studied was about back pain and muscle aches or arthritis. Many have complained that they never or always these problems. In conclusion, the higher the value of the vibration in a bus, a bus driver will feel back pain or aching muscles or joints frequently. Therefore, the vibration must always review and monitored at all times.